A chromotropic PtIIPdIICoII coordination polymer with dual electrocatalytic activity for water reduction and oxidation. Issue 41 (29th September 2021) - San Esteban, Anna Carissa M.; Kuwamura, Naoto; Yoshinari, Nobuto; Konno, Takumi
Abstract : A chromotropic coordination polymer prepared from [Pd2 Pt2 (NH3 )4 (d -penicillaminate)4 ] and Co II is reported. While both its chloride and bromide salts electrochemically catalyse water reduction, water oxidation is catalysed only by the bromide salt. Abstract : Here, we present a heterometallic coordination polymer that exhibits heterogeneous electrocatalytic activities for both water reduction and water oxidation. Treatment of the PtII2PdII2 tetranuclear complex [Pd2 Pt(NH3 )2 (d -pen)2 2 ] ([1 ]; d -H2 pen = d -penicillamine) with CoX2 (X = Cl, Br) provided (PtII2PdII2CoII2) n coordination polymers [Co2 (H2 O)6 (1 )]X4 ([2 ]X4 ), in which the PtII2PdII2 units of [1 ] are linked by [Co2 (μ-H2 O)(H2 O)5 ] 4+ moieties in a 3D network structure. [2 ]X4 showed a colour change from orange to dark green upon dehydration, reflecting the geometrical conversion of the Co II centres in [Co2 (μ-H2 O)(H2 O)5 ] 4+ from an octahedron to a tetrahedron by the removal of aqua ligands. While both [2 ]Cl4 and [2 ]Br4 electrochemically catalysed water reduction to H2 in the solid state due to the presence of Pd II active centres, water oxidation to O2 was catalysed only by [2 ]Br4, which is ascribed to the presence of Br − ions that mediate the catalytic reactions that occurred at Co II active centres.